Os Potiguara da Paraíba e o processo da (re)construção de sua identidade linguística - Jesus, Carolina Camargo de (2019)
This dissertation aims to describe how the Potiguara people (Paraíba, Brazil) (re)build its linguistic identity. In order to do this, it characterizes the processes responsible for the presence of Ancient Tupi (how they call the language they recognize as their traditional) in such community. The research also tries to emphasize the managers of the local language policy, according to Spolsky (2009). It was possible to verify that the school plays a central role in promoting the Ancient Tupi Language and that teachers are the most important managers of the local language management.